Direct Methyl Formate Formation from Methanol over Supported Palladium Nanoparticles at Low Temperature. Issue 1 (19th November 2012) - Wojcieszak, Roberto; Gaigneaux, Eric M.; Ruiz, Patricio
Abstract Palladium nanoparticles of different sizes and supported on TiO2 (2 wt. %) were synthesized by using the water‐in‐oil microemulsion method. The control of palladium nanoparticles was investigated in terms of the nature of organic surfactant and solvent. Attention was paid to the reduction of palladium ions in solution during synthesis. Materials were characterized by N2‐BET at low temperature, XRD, XPS, H2 chemisorption, and TEM and were tested in the gas phase oxidation of methanol. The results confirmed the effect of microemulsion composition on the size of palladium nanoparticles. The direct formation of methyl formate from methanol was observed. Supported palladium catalysts produced methyl formate at low temperature (<150 °C) with a very high selectivity, and, in some cases, a selectivity of approximately 100 %. At higher temperature, methyl formate is not formed at all and the total oxidation to CO2 occurs. A linear correlation between palladium particle size and methanol conversion was observed. Conversion and selectivity were correlated with the acidity of the catalysts. Very small particles were more active but less selective. A mechanism was proposed to explain the formation of methyl formate from methanol.